Enantioselective Formal Synthesis of (–)-Catharanthine through Enzyme-Catalyzed Desymmetrization of a meso-Azabicyclo [2.2.2]octane - Ikeda, Kotaro; Harada, Shingo; Hashimoto, Yoshinori; Homma, Haruka; Kono, Masato; Zumbrägel, Nadine; Gröger, Harald; Nemoto, Tetsuhiro (Synlett, 2023)
Iboga-type indole alkaloids are a promising compound group of potentially effective drugs. The common indole-fused pentacyclic skeleton is composed of an isoquinuclidine, and both enantiomers of this architecture are naturally present. In this study, we used enzymatic desymmetrization to obtain an optically active isoquinuclidine possessing four chiral carbon centers from a prochiral diester in one step. In addition, we synthesized a pentacyclic intermediate for catharanthine in an enantioenriched form through the late-stage construction of the common Iboga scaffold.
Keywords: enzymatic desymmetrization; desymmetrization; carbenes; enantioselective synthesis; alkaloids; isoquinuclidines